The Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) mRNA Vaccine-Breakthrough Infection Phenotype Includes Significant Symptoms, Live Virus Shedding, and Viral Genetic Diversity. (12th June 2021) - Pollett, Simon D; Richard, Stephanie A; Fries, Anthony C; Simons, Mark P; Mende, Katrin; Lalani, Tahaniyat; Lee, Tida; Chi, Sharon; Mody, Rupal; Madar, Cristian; Ganesan, Anuradha; Larson, Derek T; et al.
Abstract: Little is known about severe acute respiratory syndrome coronavirus 2 "vaccine-breakthrough" infections (VBIs). Here we characterize 24 VBIs in predominantly young healthy persons. While none required hospitalization, a proportion endorsed severe symptoms and shed live virus as high as 4.13 × 10 3 plaque-forming units/mL. Infecting genotypes included both variant-of-concern (VOC) and non-VOC strains.